1998
DOI: 10.1159/000028682
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Variant of a Growing Skull Fracture in an Adolescent

Abstract: A great majority of growing skull fractures occur in infancy and earlychildhood. Since the growth of brain is necessary as a driving force for these lesions to occur, almost all reported cases have been before the first 3 years of life. Although a number of uncommon locations, such as basiooccipital and skull base areas, have been reported, they are commonly located on calvaria. The authors report a growing skull fracture on the orbital roof in a 16-year-old female admitted to hospital with complaints of heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…In an extensive review of the relevant literature, we found that six cases of growing fractures of the orbital roof have previously been reported (table 1) [14, 15, 16, 17, 18, 19]. The patients with orbital roof growing fractures presented with diplopia, swollen eyelid, displaced globe and restricted eye movements after a latent silent period of varying length [14, 15, 16, 17, 18, 19]. Characteristically, none of the patients had a decline in visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive review of the relevant literature, we found that six cases of growing fractures of the orbital roof have previously been reported (table 1) [14, 15, 16, 17, 18, 19]. The patients with orbital roof growing fractures presented with diplopia, swollen eyelid, displaced globe and restricted eye movements after a latent silent period of varying length [14, 15, 16, 17, 18, 19]. Characteristically, none of the patients had a decline in visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…2,[9][10][11][12] Although the majority of patients present with complaints 2 to 12 months after the traumatic event, delay in presentation for 8 to 20 years has been reported. 2,13 In the authors' case, the patient presented 44 years after the initial injury. Because the clinical presentation can vary significantly, a classification scheme has been suggested to clarify the different pathologic processes.…”
Section: Discussionmentioning
confidence: 91%
“…On rare occasions, it has been observed in adolescence or adulthood [7, 8]. In most cases, children with simple 0,;0,-C59:413XX02CPSlinear skull fractures undergo an uneventful course of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This leptomeningeal cyst coupled with the outward force of a rapidly expanding infant brain augments the mechanical stress on the overlying bone and underlying cortex. CSF hydrodynamic features have also been implicated in the genesis of leptomeningeal cysts [7]. It has been hypothesized that the pulsatile force exerted on the ventricular wall encounters less resistance owing to the absence of dura and bone at the site of injury.…”
Section: Discussionmentioning
confidence: 99%